2023
DOI: 10.3389/fonc.2022.1061789
|View full text |Cite
|
Sign up to set email alerts
|

Facts and Perspectives: Implications of tumor glycolysis on immunotherapy response in triple negative breast cancer

Abstract: Triple negative breast cancer (TNBC) is an aggressive disease that is difficult to treat and portends a poor prognosis in many patients. Recent efforts to implement immune checkpoint inhibitors into the treatment landscape of TNBC have led to improved outcomes in a subset of patients both in the early stage and metastatic settings. However, a large portion of patients with TNBC remain resistant to immune checkpoint inhibitors and have limited treatment options beyond cytotoxic chemotherapy. The interplay betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 141 publications
0
4
0
Order By: Relevance
“…Due to metabolic reprogramming, cancer cells exhibit high glycolysis rates, resulting in lactate overproduction and increased extracellular acidity [ 18 ]. In addition, tumor glycolysis and lactate production affect the tumor immune microenvironment through metabolic competition with infiltrating immune cells [ 19 ]. Therefore, targeting glycolysis has become a promising direction for tumor therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Due to metabolic reprogramming, cancer cells exhibit high glycolysis rates, resulting in lactate overproduction and increased extracellular acidity [ 18 ]. In addition, tumor glycolysis and lactate production affect the tumor immune microenvironment through metabolic competition with infiltrating immune cells [ 19 ]. Therefore, targeting glycolysis has become a promising direction for tumor therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is a predominantly glycolytic malignancy [150] involved in tumor progression [151] and resistance to therapy [152]. Supporting these observations are the experiments of Godoy et al [153] who found that 90% of breast cancers had a high or very high expression of the glucose transporter 1 and 2 (GLUT1, GLUT2) which means that they have a high glycolytic flux.…”
Section: Breast Cancermentioning
confidence: 95%
“…Breast cancer is a malignancy characterized predominantly by glycolytic metabolism [ 150 ], which is involved in tumor progression [ 151 ] and resistance to therapy [ 152 ]. Supporting these observations are the experiments of Godoy et al [ 153 ], who found that 90% of breast cancers had high or very high expression of glucose transporters 1 and 2 (GLUT1 and GLUT2), which means that they have a high glycolytic flux.…”
Section: Experimental Evidence For Dca Activity In Cancermentioning
confidence: 99%